Why the Utilization of E-Government Services is Poor? – A study with the Citizens in Colombo Municipal Council Area in Sri Lanka - Withanage, U P A; Gunawardene, Lasith; Endagamage, Dileepa M (Integrated Journal for Research in Arts and Humanities, 2022)
One of the most important elements of an e-Government system is the interaction between users and e-Government systems, specifically the adoption and utilization by those users, who are the main target of such systems. However, even after taken numerous efforts to develop an e-service system in Sri Lanka, its utilization and adoption are still at a very poor level. It indicates as the rate of online submission of applications is 1.16% and for license/ permits it is 0.18%. Thus, this research aims to investigate, analyze and understand the key factors that influence users’ adoption and utilization of two e-Government services: e-Vehicle revenue license and e-Police clearance certificate in Sri Lanka with a holistic approach. The conceptual framework was developed by studying the Technology Acceptance Model (TAM) and Web Trust models and theories related to technology acceptance and usage, in conjunction with a review of e-Government adoption and utilization literature. The study population was the Colombo Municipal Council area with 561,314 individuals. A random sample of 203 chief occupants was selected and the response rate was 96.5%. Respondents’ demographic details, educational qualifications, internet experience, e-Government usage and as well as preferences when obtaining e-Government services were included. The results showed significant (5% level) moderate positive relationships among utilization and “usefulness”, “ease of use”, “trust in the internet” and “trust in the Government”. Moreover, “usefulness” (β=0.445) and “trust of the government” (β=0.379) were found to be the significant (5% level) influential factors in adoption and utilization with model adequacy at 36.5%. Similar to the literature, the findings ensure that when the usefulness and the trust are at a higher level, the adoption and utilization also be at a higher level. The- challenges for citizen-centered e-Government applications were identified as a lack of users’ trust in the internet service providers, level of security standards, quality of e-Government systems, reluctance to share, exchange, and store their personal information specially the financial information in the online platform. However, the positive factor is the citizens perceive and experience e-Government systems as simple to use and useful. Further, they intend to accept and use it. Based on the interviews held with the uses, implementing simple and useful e-services and e-transactions, enhancing the reliability of the services, improving the accessibility options of the implemented e-services and e-transactions, and increasing the awareness of implemented e-services and their benefits were highlighted as their suggestions to develop the existing e-Government systems and services in Sri Lanka. The most important fact emphasized here is the implementation of a one-stop e-Government portal for all the services. Actions taken to enhance the digital literacy of the citizens from their school level will be benefited to successful adoption and utilization of e-services in Sri Lanka.